IFN‐λ‐mediated IL‐12 production in macrophages induces IFN‐γ production in human NK cells. Issue 1 (10th November 2014) - de Groen, Rik A.; Boltjes, Arjan; Hou, Jun; Liu, Bi‐Sheng; McPhee, Fiona; Friborg, Jacques; Janssen, Harry L. A.; Boonstra, André
<x xml:space="preserve">Abstract</x> With increasing interest in alternative options to interferon‐alpha‐based treatments, IFN‐λ has shown therapeutic promise in a variety of diseases. Although the antiviral activity of IFN‐λ has been extensively studied, there is limited knowledge regarding the immunological functions of IFN‐λ and how these differ from those of other classes of IFNs. In this study, we investigated the effects of IFN‐λ on primary human NK cells, both in a direct and indirect capacity. We demonstrate that in contrast to interferon‐alpha, IFN‐λ is unable to directly stimulate NK cells, due to the absence of IFN‐λ receptor chain 1 (IFN‐λR1) on NK cells. However, IFN‐λ, in combination with TLR4 challenge, is able to induce the production of select members of the IL‐12 family of cytokines in monocyte‐derived macrophages. We further show that through macrophage‐mediated IL‐12 production, IFN‐λ is able to indirectly affect NK cells and ultimately induce IFN‐γ production.